Attitudes and related psychosocial constructs : theories, assessment, and research - Aiken, Lewis R., 1931- (Sage Publications, 2002)
In this work, the author provides a compact but comprehensive research-oriented treatment of attitudes and related psychosocial constructs - values, opinions, beliefs, and personal orientations.